A Randomized Phase II/III Trial Evaluating the Efficacy and Safety of 100 and 125 µg of Calcifediol Weekly Treatment of Severe Vitamin D Deficiency - Pérez-Castrillón, Jose Luis; Jódar-Gimeno, Esteban; Nociar, Ján; Lojka, Michal; Nikolov, Dimitar; Cereto-Castro, Fernando; Novković, Snežana; Tarantino, Umberto; Mehsen-Cetre, Nadia; Arranz, Paula; Martínez Ostalé, Cristina; García-Bea, Aintzane; et al. (Nutrients, 2025)
Background/Objectives: Given the crucial health benefits of vitamin D, addressing severe deficiencies is a pressing medical concern. This study aimed to evaluate the effectiveness and safety of two new weekly doses of calcifediol (100 µg and 125 µg) for long-term management in patients with severe vitamin D deficiency, defined as plasma 25(OH)D levels ≤10 ng/mL. Methods: This study was a randomized, two-cohort, controlled, double-blind, multicentre phase II-III trial. Subjects were randomized 2:2:1 to weekly calcifediol 100 µg, 125 µg or a placebo. The primary endpoint was the proportion of patients achieving plasma 25(OH)D levels of ≥20 ng/mL and/or ≥30 ng/mL by week 16. Results: A total of 276 patients (mean age: 55.2 years, SD 15.42) were randomized. By week 16, 92.3% and 91.8% of patients in the calcifediol 100 µg and 125 µg groups, respectively, reached ≥20 ng/mL, compared to 7.3% in the placebo group. Levels of ≥30 ng/mL were achieved by 49% (100 µg) and 76.4% (125 µg) of participants, with none in the placebo group. Calcifediol demonstrated superior efficacy at all response levels and time points (p < 0.0001). Plasma 25(OH)D concentrations increased by week 24 and remained stable. The incidence of adverse events was comparable across groups. Conclusions: A weekly calcifediol dose of 100 µg demonstrates the best profile of efficacy and tolerability, providing a reliable solution for achieving and maintaining adequate vitamin D levels in patients with severe deficiency.
Keywords: rozvrh dávkování léků; dospělí; safety; Female; Calcifediol; Adult; výsledek terapie; ženské pohlaví; vitamin D deficiency; kalcifediol; lidé; dvojitá slepá metoda; vitamin D; Drug Administration Schedule; nedostatek vitaminu D; Treatment Outcome; Vitamin D; Double-Blind Method; Male; Aged; calcifediol; Vitamin D Deficiency; lidé středního věku; senioři; mužské pohlaví; weekly treatment; Middle Aged; efficacy; Humans